(3cJGH aj JGQjN GdeZQHs
(3ChdgG (B:s
(3dGdMeO ddg GdPj LYd jaNQ HLRjQI GdGfOdS edF ajg CeG HYO aEfg MQc efj SGcfG hedG aj aGQZkG aNQHJ Yf SLjJj s
(3BNQgG (B:s
(3aGdMeO ddg GdPj GWdY ef GdeYQH gPg GdTehS hLYdgG Hjf LejY Cgd HefRdI GdQDS s
(3Vef eLehY , JQJjHgG (B: 3s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs